Analisis Sistem Informasi Manajemen Keuangan di UMKM - Nurul Huda; Ratih Kusumastuti; Achmad Hizazi (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2025)
Digital transformation in the field of information technology requires Micro, Small, and Medium Enterprises (MSMEs) to improve the quality of financial management to be able to compete sustainably. One effort that can be done is through the implementation of the Financial Management Information System (MISK). This study aims to analyze the implementation of MISK in MSMEs, examine the benefits obtained, and identify obstacles faced in the implementation process. The research method used is a qualitative descriptive approach with data collection techniques through interviews, observation, and documentation. The object of the study is the culinary MSME "Dapur Lestari Jambi" which has implemented a digital financial recording application and Point of Sale (POS) system. The results of the study indicate that the implementation of MISK can increase the accuracy of transaction recording, accelerate the preparation of financial reports, improve cash flow management, and support data-based managerial decision-making. However, the implementation of MISK still faces several obstacles, especially related to limited human resource competency, consistency of recording, and adaptation to technology. This study concludes that the Financial Management Information System has a strategic role in increasing the efficiency, transparency, and professionalism of MSME financial management, and is an important factor in supporting business sustainability in the digital era.